Ramble Bahamas: Pioneering Bahamian History & Culture in the Digital Age - Dawson, Jessica R.; Thompson, Tracey L. (International Journal of Bahamian Studies, 2017)
The digital humanities offer a unique vehicle for bridging the past and present. Interactive media formats encourage user engagement while maintaining the integrity of historical methodologies. Digital platforms enable audiences located far and wide to access information that is not easily available in print format. All these advantages carry special value for students, educators, and scholars who are investigating twentieth-century Bahamian history. Such audiences are met with a grave shortage of resources, whether in physical format or web-based format, which illuminate the Bahamian experience. The challenge of accessing resources confronts, in particular, audiences which are located within the Bahamian archipelago yet outside the central island of New Providence as well audiences that are located abroad. Ramble Bahamas seeks to remedy this deficit by providing a curated collection of easily accessible place-based exhibits in an innovative medium. Each geo-tagged exhibit includes a cohesive narrative which centers on the story of an historically significant site or object. Additional context is built through the inclusion of historical images, newspapers, other documents, and contemporary photographs. Select audio clips taken from oral history interviews with authoritative narrators are also featured within each exhibit to deepen the sense of place, further stimulate the sensory experience of the visitor, and extend each visitor’s knowledge about events associated with the location and about circumstances prevailing during the era. Techniques for constructing the product include carrying out oral history interviews, conducting documentary and archival research, and performing audio-visual digitization and editing, as well as deploying and customizing the Omeka content management system powered by Curatescape.